Design of Medium Power AC-DC Flyback LED Driver - Yoppy Yoppy; Siddiq Wahyu Hidayat; Hutomo Wahyu Nugroho; Tyas Ari Wahyu Wijanarko; Elvina Trivida; Priyo Wibowo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
LED lighting market share shows an ever increasing trend. This is driven by some of the LED advantages, such as higher efficiency, wide range of colors, and longer lifetime. LED is a DC device, and to power it from AC supply, like in household or street lightings, a driver is required to convert AC to DC supply. In addition, LED driver is preferred to operate in constant current mode in order to avoid LED thermal runaway. Also the driver has to have high efficiency, low THD (total harmonic distortion), and comply with electromagnetic emission limits. In this paper, a prototype of primary-side-regulated AC-DC flyback LED driver has been implemented. It has a constant output current of 0.990A 0.012A across the output voltage 15.59V – 42.80V. Measurement results show that the achieved efficiency is up to 88.55%, current harmonics comply with IEC 61000-3-2, and conducted emission levels comply with CISPR 15.